Ineficacia de la suspensión de la ejecución de la pena en la resocialización del condenado - Cerdeña del Aguila, Ana María (2020)
This study was aimed at analysing the extent to which the ineffective application of the suspension of the execution of the sentence established in the Criminal Code affects the resocialization of the convicted person. An investigation of applied type, observational, transversal design, whose logical inductive-deductive method. The questionnaire, the interview and the analysis form were used as measurement instruments to gather information and measure the study variables. The sample was made up of 165 law professionals and 69 sentences on suspended sentences. The results obtained made it possible to establish that: Probably the ineffective application of the suspension of the execution of the sentence established in the Criminal Code affects the re-socialization of the convicted person, Tacna 2015-2018.